HUBUNGAN PAPARAN TUNGAU DEBU RUMAH DENGAN URTIKARIA DAN/ATAU ANGIOEDEMA PADA ANAK DI PANTI ASUHAN KECAMATAN PAUH KOTA PADANG - Muhammad Rafif Sulthan Habibi; Selfi Renita Rusjdi; Gardenia Akhyar; Adrial Adrial; Qaira Anum; Dwitya Elvira (SINERGI : Jurnal Riset Ilmiah, 2026)
Urticaria is a skin condition characterized by wheals, which may be accompanied by itching, a burning sensation, or pain, and can occur together with angioedema. House dust mites (HDM) are one of the main aeroallergens capable of triggering IgE-mediated allergic skin reactions. Children living in crowded environments, such as orphanages, are at high risk of HDM exposure. This study aimed to determine the relationship between house dust mite exposure and the occurrence of urticaria and/or angioedema in children at an orphanage in Pauh District, Padang City. This was an observational analytical study with a cross-sectional approach, conducted at an orphanage in Pauh District, Padang City, and in the Parasitology Laboratory of the Faculty of Medicine, Andalas University, from March to October 2025. The sampling technique used was total sampling. Bed dust was collected using a vacuum cleaner, and interviews were conducted using an adapted UAS and ISAAC questionnaire. Chi-square was used to analyze the relationship between the two variables. The results of this study showed that all dust samples (100%) were positive for house dust mites, and identification revealed that the most common species found was Dermatophagoides sp. (57.14%), followed by Acarus sp. (32.14%), Cheyletus sp. (25%), Carpoglyphus sp. (17.86%), Glycyphagus sp. (14.29%), Thyrophagus sp. (14.29%), and Blomia tropicalis (7.14%). The average density of house dust mites was 72.85 mites/gram of dust. The prevalence of urticaria and/or angioedema in children was 25.6%. This study found no significant association between house dust mite density and the occurrence of urticaria and/or angioedema (p = 0.263). The conclusion of this study is that factors such as individual predisposition, environmental conditions, and immune sensitization status are likely to contribute to the development of urticaria and/or angioedema.